DOES MILD HEPATITIS ON LIVER BIOPSY WARRANT IMMEDIATE COMBINATION ANTI VIRAL THERAPY IN CHRONIC HEPATITIS C PATIENTS? - Khalid, Shahid Raza; Luk, Nasir Hassan; Mirza, Shakil Ahmed; Saeed, Farrukh; Hashmi, Shoaib Nayyar; Mushtaq, Sajid; Tanvir, Amjad; Rana, Waris Ali (Journal of Ayub Medical College Abbottabad, 2010)
Background: Not all patients with histologically mild chronic Hepatitis C progress to cirrhosis. Many patients being treated on the basis of raised ALT and positive PCR alone may not be actually requiring it. Methods: All adult patients suffering from chronic Hepatitis C, qualifying for combination interferon ribavirin therapy, under went liver biopsies. Tissue samples were sent to Armed Forces Institute of Pathology (AFIP) Rawalpindi for histopathology. Reporting was done according to modified Ishaq score. Results: Total number of patients was 147. Out of these, 75 (51%) were female and 72 (49%) were male. Mean age of females and males were 35.1±8.12 and 36.31±8.56 year respectively. Out of these, 19 (12.9%) were stage zero, 61 (41.5%) at stage 1, and 31 (21.1%) at stage 2 of modified fibrotic Ishaq score. In all, 111 (75.5%) of the patients were ‰¤2 of modified Ishaq fibrotic score in either sex or 80 (54.4%) ‰¤1 of modified Ishaq fibrotic stage. The necroinflammatory score has been divided into minimal (0-3), mild (4-8), moderate (9-13), and severe (14-18). About the same number of our patients (74%) had minimal to mild inflammation. Conclusion: Since the majority of the patients have fibrotic score less than 3, so it will be cost effective to individualise their treatment on liver histpathology. Patients with low fibrotic score and minimal to mild inflammation may not be treated, but only monitored with serial ALT and liver biopsy every 4-5 years. Treatment may be started if there is increase in fibrosis on surveillance biopsy. However, there is a need to conduct prospective studies in similar group of patients to evaluate the natural course of disease in untreated patients. Keywords: liver biopsy, chronic liver disease, HAI score, HCV